Exploring the Antimicrobials Production Potential of Actinobacteria Isolated from Caves at Bahadurkhel Karak, Pakistan: Antimicrobial activities of cave actinobacteria against XDR Salmonella - Nawaz, Shahid; Fatima, Aiman; Saleem, Maira; Sajid, imran (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Cave actinobacteria are relatively less explored and are considered as the new targets for the discovery of novel antimicrobials, specifically against highly resistant pathogens such as extensively drug-resistant (XDR) Salmonella. In this study N=20 actinobacteria isolates were retrieved from the least disturbed caves situated at Bahadurkhel Karak, Pakistan (33° 16’ 52” North, 70° 79’ 07” East) and (33° 15’ 90” North, 70° 94’ 72” East). The isolates were identified using standard morphological and biochemical characterization procedures as well as by 16S rDNA sequencing. N= 16 isolates were targeted for further antimicrobial activity screening based on their preliminary morphological and biochemical identification. The methanolic extracts were prepared from the culture broth of the isolates by using Amberlite® XAD-16 resin to execute in situ solid phase extraction. The thin layer chromatography (TLC) showed the presence of a variety of different compounds in the crude extracts of the secondary metabolites. The extracts’ antimicrobial potential was analyzed against several test strains, including Salmonella enterica, Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae, and Escherichia coli. Among the isolated strains, the isolates SNK 93 and SNK47 were found to be the most active against the tested pathogenic bacteria, showing growth inhibition zones of 20 mm and 27 mm respectively against extensively drug-resistant (XDR) Salmonella. Based on these results it can be concluded that cave actinobacteria are a promising source of potentially novel antimicrobials against multidrug-resistant (MDR) and XDR pathogens.